2021
DOI: 10.1186/s12955-021-01739-3
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in primary sclerosing cholangitis: a systematic review

Abstract: Background Primary sclerosing cholangitis (PSC) is a rare bile duct and liver disease which can considerably impact quality of life (QoL). As part of a project developing a measure of QoL for people with PSC, we conducted a systematic review with four review questions. The first of these questions overlaps with a recently published systematic review, so this paper reports on the last three of our initial four questions: (A) How does QoL in PSC compare with other groups?, (B) Which attributes/fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…1 The disease burden that is associated with PSC is thought to have a significant effect on health-related quality of life (HRQoL), although only limited evidence is available. 3 Proper estimation of HRQoL of PSC patients is needed for various purposes such as disease burden estimation, treatment evaluation in daily clinical practice and clinical trials, and for health-economic evaluation of new interventions. Both the US Food and Drug Administration and the European Medicines Agency have stressed the importance of HRQoL as an outcome measure in chronic diseases such as PSC.…”
Section: Introductionmentioning
confidence: 99%
“…1 The disease burden that is associated with PSC is thought to have a significant effect on health-related quality of life (HRQoL), although only limited evidence is available. 3 Proper estimation of HRQoL of PSC patients is needed for various purposes such as disease burden estimation, treatment evaluation in daily clinical practice and clinical trials, and for health-economic evaluation of new interventions. Both the US Food and Drug Administration and the European Medicines Agency have stressed the importance of HRQoL as an outcome measure in chronic diseases such as PSC.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to include patient-reported outcomes (PROs), such as QoL, in clinical research to ensure that the safety and efficacy of new treatments is assessed holistically [ 9 ]. Our recent review found very few PSC clinical trials which assessed QoL [ 10 ]. In our review we also observed that generic QoL questionnaires may lack sensitivity and fail to measure important impacts of PSC, such as fatigue, and that surrogate endpoints commonly used in trial settings (e.g.…”
Section: Introductionmentioning
confidence: 99%